2016
DOI: 10.1111/pde.12840
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Eczematoid Graft‐Versus‐Host Disease

Abstract: A 13-year-old boy underwent allogeneic hematopoietic stem cell transplantation (HSCT) for underlying acute lymphoblastic leukemia and achieved neutrophil engraftment 28 days after HSCT. He developed ichthyosis 6 weeks after HSCT and then keratotic follicular papules, palmoplantar keratoderma, and a seborrheic dermatitis-like eruption 18 weeks after HSCT. From skin biopsies he was diagnosed with eczematoid graft-versus host disease (GVHD), which showed spongiosis with scattered necrotic keratinocytes. He respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…Eczema-like GVHD has been previously described as an atypical form of GVHD, 1 affecting both pediatric and adult patients, ranging in age from 1.5 to 65 years. [10][11][12][13] Creamer et al reported 10 patients with widespread eczematous eruptions in a background of chronic GVHD following HCT, and described this presentation as "eczematoid GVHD," 10 showing an aggressive chronic clinical course and poor prognosis. All patients in this series developed erythroderma and six patients died either from infection (n = 5) or from the relapse of the background hematolymphoid disease (n = 1).…”
Section: Patientmentioning
confidence: 99%
See 4 more Smart Citations
“…Eczema-like GVHD has been previously described as an atypical form of GVHD, 1 affecting both pediatric and adult patients, ranging in age from 1.5 to 65 years. [10][11][12][13] Creamer et al reported 10 patients with widespread eczematous eruptions in a background of chronic GVHD following HCT, and described this presentation as "eczematoid GVHD," 10 showing an aggressive chronic clinical course and poor prognosis. All patients in this series developed erythroderma and six patients died either from infection (n = 5) or from the relapse of the background hematolymphoid disease (n = 1).…”
Section: Patientmentioning
confidence: 99%
“…11 Other isolated case reports have described eczema-like GVHD in patients who have shown a good response to treatment with complete remission of the disease. 12,13 The average time to presentation following HCT in reported cases of "eczematoid"…”
Section: Patientmentioning
confidence: 99%
See 3 more Smart Citations